JEJARING KEBIJAKAN PARIWISATA BUDAYA DI DESA LEWOKLUOK KABUPATEN FLORES TIMUR - Kristianus Molan (Jurnal PubBis, 2022)
This paper aims to explain the portrait of cultural tourism in Lewokluok Village, East Flores Regency after the Anugerah Pesona Indonesia (API) Awards. By utilizing the perspective of policy networking qualitative research seeks to map the key actors, decision-making arena and institutionalization of policy networking. The results showed that government and community actors have an equal position in the process of aggregation of interests and decision making. Decision making is carried out in a formal arena at the district and village levels. The collaboration of government and community actors creates interdependent relationships and spaces for reciprocal use of resources. In this system, local communities become the main actors in managing Village Cultural Tourism, receiving the benefits of knowledge, skills and capital. Government actors as facilitators benefit in increasing local revenue. In concrete terms, cultural tourism activities in Lewokluok Village, East Flores Regency seeks to implement collaborative tourism development practices for the welfare of the wider community.